Cotreatment with sorafenib and oleanolic acid induces reactive oxygen species-dependent and mitochondrial-mediated apoptotic cell death in hepatocellular carcinoma cells. Issue 3 (March 2019) - Liese, Juliane; Hinrichs, Tobias M.; Lange, Matthias; Fulda, Simone
Abstract : Hepatocellular carcinoma (HCC) is the most common liver malignancy, and the lack of effective chemotherapies underlines the need for novel therapeutic approaches for this disease. Recently, we discovered a novel synergistic induction of cell death by combining sorafenib, the only routinely used palliative chemotherapeutic agent, and the triterpenoid oleanolic acid (OA). However, the underlying mechanisms of action have remained obscure. Here, we report that sorafenib and OA acted in concert to trigger mitochondria-mediated apoptotic cell death, which is dependent on reactive oxygen species (ROS). Sorafenib/OA cotreatment significantly increased ROS production, which was prevented by the ROS scavengers α-tocopherol and MnTBAP. Importantly, rescue experiments showed that ROS were required for sorafenib/OA-induced apoptosis as ROS scavengers protected HCC cells against cell death. In addition, sorafenib and OA cotreatment cooperated to decrease myeloid cell leukaemia-1 expression and to activate Bak, two events that were prevented by ROS scavengers. Bak activation was accompanied by the loss of mitochondrial membrane potential, followed by PARP cleavage, DNA fragmentation and, finally, apoptotic cell death in HCC cells. By providing new insights into the molecular regulation of sorafenib/OA-mediated and ROS-dependent cell death, our study contributes toward the development of novel treatment strategies to overcome sorafenib resistance in HCC. Abstract : Supplemental Digital Content is available in the text.